2022
DOI: 10.3390/molecules27144368
|View full text |Cite
|
Sign up to set email alerts
|

Antioxidant and Gastroprotective Activity of Suaeda fruticosa Forssk. Ex J.F.Gmel

Abstract: Suaeda fruticosa Forssk. Ex J.F.Gmel is traditionally used for inflammatory and digestive disorders, as a carminative, and for diarrhea. This plant is widely distributed in Asia, Africa, and the Mediterranean region. Aqueous methanolic extract of S. fruticosa (Sf.Cr) was prepared and screened for phytoconstituents through qualitative and GC-MS analysis. Quantification of total phenolic and flavonoid contents was performed, while antioxidant capacity was determined by DPPH, CUPRAC, FRAP, and ABTS assays. The ga… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 44 publications
(44 reference statements)
0
3
0
Order By: Relevance
“…The results from FRAP assay further confirmed the antioxidant activity of TS. Therefore, the anti-gastric ulcer actions of TS might be partly related to its antioxidant property [ 68 , 69 ]. From the previous studies, it was found that each plant component in TS remedy has been reported to possess the antioxidant properties [ 17 ].…”
Section: Discussionmentioning
confidence: 99%
“…The results from FRAP assay further confirmed the antioxidant activity of TS. Therefore, the anti-gastric ulcer actions of TS might be partly related to its antioxidant property [ 68 , 69 ]. From the previous studies, it was found that each plant component in TS remedy has been reported to possess the antioxidant properties [ 17 ].…”
Section: Discussionmentioning
confidence: 99%
“…Total phenolic contents (TPC) of the Lp.Cr were determined by using Folin-Ciocalteau assay [ 25 ]. Calibration curve was plotted with gallic acid (7.8–1000 μg/ml).…”
Section: Methodsmentioning
confidence: 99%
“…Total flavonoid contents (TFC) of Lp.Cr were determined as described previously [ 25 ]. Quercetin (7.8–500 μg/ml) was used to draw the calibration curve.…”
Section: Methodsmentioning
confidence: 99%
“…A standard curve of quercetin (concentration ranging from 7.81 to 500 mg/mL, 2-fold dilution) was drawn under the same procedure. Flavonoid contents were expressed in milligram equivalent to quercetin per gram of dry extract (mg QE/g) [79].…”
Section: Quantitative Analysis Of Total Phenols Tannins Flavonoids An...mentioning
confidence: 99%